Exploring the prevalence and burden of sleep disturbance in primary brain tumor patients. Issue 6 (22nd June 2022) - King, Amanda L; Shuboni-Mulligan, Dorela D; Vera, Elizabeth; Crandon, Sonja; Acquaye, Alvina A; Boris, Lisa; Burton, Eric; Choi, Anna; Christ, Alexa; Grajkowska, Ewa; Jammula, Varna; Leeper, Heather E; et al.
Abstract: Background: Sleep disturbance (SD) is common in patients with cancer and has been associated with worse clinical outcomes. This cross-sectional study explored the prevalence of SD in a primary brain tumor (PBT) population, identified associated demographic and clinical characteristics, and investigated co-occurrence of SD with other symptoms and mood disturbance. Methods: Demographic, clinical characteristics, MD Anderson Symptom Inventory-Brain Tumor, and Patient Reported Outcome Measurement Information System Depression and Anxiety Short-Forms were collected from PBT patients at study entry. Descriptive statistics, Chi-square tests, and independent t -tests were used to report results. Results: The sample included 424 patients (58% male, 81% Caucasian) with a mean age of 49 years (range 18–81) and 58% with high-grade gliomas. Moderate-severe SD was reported in 19% of patients and was associated with younger age, poor Karnofsky Performance Status, tumor progression on MRI, and active corticosteroid use. Those with moderate-severe SD had higher overall symptom burden and reported more moderate-severe symptoms. These individuals also reported higher severity in affective and mood disturbance domains, with 3 to 4 times higher prevalence of depressive and anxiety symptoms, respectively. The most frequently co-occurring symptoms with SD were, drowsiness, and distress, though other symptoms typically associated with tumor progression also frequently co-occurred. Conclusions: PBT patients with moderate-severe SD are more symptomatic, have worse mood disturbance, and have several co-occurring symptoms. Targeting interventions for sleep could potentially alleviate other co-occurring symptoms, which may improve life quality for PBT patients. Future longitudinal work examining objective and detailed subjective sleep reports, as well as underlying genetic risk factors, will be important.